The Timing Analysis of Inheritance Distributions in the Compilation of Islamic Law - Azni, Azni; Rifqi, Muhammad Akhyar; Saifunnajar, Saifunnajar; Syu'aib, Kholil; Mohd. Zin, Najibah Bt (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
This study discussed about the distribution time of inherited property after the death of a person that is not explained explicitly in Islamic family law in Indonesia particularly in the Compilation of Islamic Law. This study aimed to critically analyze the time of inheritance distribution in the Compilation of Islamic Law viewed from maqasid sharia perspective. The research employed qualitative research method, namely library legal research. The data collection technique was documentation, included the Compilation of Islamic Law, fiqh books, books of legislation in the field of Islamic law which were applicable in Indonesia. The data were analyzed by using content analysis method to find out the distribution time of inheritance in the compilation of Islamic Law based on maqasid sharia perspective. The result of this research showed that the Compilation of Islamic Law did not stipulate the time of inheritance distribution explicitly, and if the determination of the inheritance distribution time is in accordance with the provisions in the compilation of Islamic law for the kindness of the family and heirs, then the action is justified by sharia law because it is in line with maqasid sharia. However, if the division of inherited property is in accordance with the provisions of the Compilation of Islamic Law with the purpose to delay the time of distribution which will result in a reduction in the value of the property, or the physical loss of the property, then it is included into the act of zalim and certainly contradicts the Islamic sharia itself. It must not be carried out.